Lithiophilic Faceted Cu(100) Surfaces: High Utilization of Host Surface and Cavities for Lithium Metal Anodes - Gu, Yu; Xu, Hong‐Yu; Zhang, Xia‐Guang; Wang, Wei‐Wei; He, Jun‐Wu; Tang, Shuai; Yan, Jia‐Wei; Wu, De‐Yin; Zheng, Ming‐Sen; Dong, Quan‐Feng; Mao, Bing‐Wei (Angewandte Chemie International Edition, 2019)
Lithium metal anodes suffer from poor cycling stability and potential safety hazards. To alleviate these problems, Li thin‐film anodes prepared on current collectors (CCs) and Li‐free types of anodes that involve direct Li plating on CCs have received increasing attention. In this study, the atomic‐scale design of Cu‐CC surface lithiophilicity based on surface lattice matching of the bcc Li(110) and fcc Cu(100) faces as well as electrochemical achievement of Cu(100)‐preferred surfaces for smooth Li deposition with a low nucleation barrier is reported. Additionally, a purposely designed solid–electrolyte interphase is created for Li anodes prepared on CCs. Not only is a smooth planar Li thin film prepared, but a uniform Li plating/stripping on the skeleton of 3D CCs is achieved as well by high utilization of the surface and cavities of the 3D CCs. This work demonstrates surface electrochemistry approaches to construct stable Li metal–electrolyte interphases towards practical applications of Li anodes prepared on CCs. Get in touch with lithium: The generation of surface lithiophilicity on planar and 3D Cu hosts for Li metal anodes is reported. Enabled by a lattice matching of Cu(100) and Li(110), smooth deposition of Li thin films and the creation of ultra‐smooth ultra‐thin SEI on the Cu hosts is made possible. This allows a high utilization of not only the surface but also cavities of the Cu hosts.